Body mass trajectories and multimorbidity in old age: 12-year results from a population-based study - Calderón-Larrañaga, Amaia; Hu, Xiaonan; Guo, Jie; Ferrucci, Luigi; Xu, Weili; Vetrano, Davide L. (Clinical nutrition (Edinburgh, Scotland), 2021)
Body weight changes reflect and impact several health conditions in older age, but little is known about its relationship with multimorbidity. We aimed to study the association of long-terms trajectories of body mass index (BMI) with contemporaneous changes in multimorbidity −and multimorbidity type− development in a population-based cohort of older adults. Twelve-year BMI trajectories (2001–2013) were identified in subjects aged 60+ years from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K) using growth mixture models (N = 2189). Information on 60 chronic diseases and multimorbidity was ascertained based on clinical examinations, lab tests, medications, and inpatient and outpatient medical records. Linear mixed models were used to study the association between BMI trajectories and the speed of chronic disease accumulation, in general and by groups of cardiovascular and neuropsychiatric diseases. Eighty percent of the study population was included in what we defined a stable BMI trajectory, 18% in a slow-decline trajectory with an accelerated BMI decline from age 78 onwards, and 2% in a fast-decline trajectory that reached underweight values before age 85. A significantly higher yearly rate of chronic disease accumulation was observed in the fast-decline versus stable trajectory (β = 0.221, 95% CI 0.090–0.352) after adjusting the model for age cohort, sex, education and time to death. Subjects in the slow-decline trajectory showed a significantly higher yearly rate of cardiovascular disease accumulation (β = 0.016, 95% CI 0.000–0.031); those in the fast-decline trajectory showed a faster accumulation of both cardiovascular (β = 0.020, 95% CI -0.025, 0.064) and neuropsychiatric diseases (β = 0.102, 95% CI 0.064–0.139), even if the former association did not reach statistical significance. Our results provide further evidence of the importance of carefully monitoring older adults with sustained weight loss, which is an early indicator of accelerated health deterioration, reflected in our study by a faster accumulation of chronic −especially neuropsychiatric− diseases.